Capitalizing on Change : A Social History of American Business - Buder, Stanley (Book collections on Project MUSE., 2009)
Americans love "this year's model," relying on the "new" to be always "improved." Enthusiasm for the new, says Stanley Buder, is essential to American business, where innovation and change stoke the engines of economic energy. To really understand the history of business in America, he argues, we must understand the intertwining dynamics of social and business values. In a history spanning over three hundred years, Buder examines the enveloping expansion of the market economy, the laggardly use of government to modify or control market forces, the rise of consumer.